Development of an Objective Structured Clinical Examination to Assess Medical Student Competence in the Ocular Examination - Knoch, Daniel W. (Journal of Academic Ophthalmology, 2014)
Purpose Competently performing the ocular examination is an essential skill of every graduating medical student. Assessment of competence in performing the ocular examination is equally essential. Unfortunately, there is a paucity of tools useful in assessing clinical competence in ophthalmology. The Objective Structured Clinical Examination (OSCE) format has been shown to be a useful tool to assess clinical competence in other academic settings. It is hypothesized that the OSCE format can be used to assess clinical competence in performing the ocular examination. This study presents the novel use of the OSCE format for assessing competence in obtaining a history of headache and performing the ocular examination by third and fourth year medical students. Methods Observational design was used to assess the competence of third and fourth year medical students in taking a brief history on the chief complaint of headache and performing the ocular examination. The ophthalmology OSCE was used after a one-week ophthalmology clerkship at the University of Wisconsin-Madison School of Medicine and Public Health. Standardized patients were trained by ophthalmology staff prior to the OSCE. The standardized patients were not dilated for the direct ophthalmoscope portion of the examination. Results Students were graded on their performance in obtaining a history of headache and performing the ocular examination. The ocular examination included assessment of ocular motility, pupils, using confrontation to find a visual field defect, and using the direct ophthalmoscope to match a standardized patient's optic nerve to one of four photos in the room. A check box system was used to assess the student's competence. This was reported as pass, marginal, or fail. Failing students were remediated by an ophthalmologist. A total of 384 students took the exam from 2008 to 2012. Overall, 84% received a passing score, 11% received a marginal score, and 5% received a failing score. Conclusion Establishment of competence and assessment of competence continue to be a major focus of medical student education. The OSCE format provides a standardized testing platform to assess competence with performing the ocular examination. Use of standardized patients provides a more natural format than paper-based or other methods of assessment.
Keywords: OSCE; assessment; medical students; evaluation; fundoscopy